Epidemiological and Clinical Characteristics of Hepatitis C Viral Infections in Tertiary Centres in Sulaimani City / Kurdistan Region of Iraq - Hama Rahim, Bestun Rahim; Hussain, Ali Hattem; Mohammed, Mohammed Omer; Rashid, Kamal Jalal (Kurdistan Journal of Applied Research, 2017)
Hepatitis C infection is one of the most common causes of chronic liver disease. It is growing threat and main burden on public health. Globally more than 170 million people are infected with hepatitis C virus (HCV), up to 4 million new infections annually and each year more than 350000 dies of HCV related complications, including cirrhosis and hepatocellular carcinoma (HCC). Thus this descriptive case-series study was conducted in five health facilities in Sulaimani city, from 23rd December 2015 to 10th of June 2016. The data were collected from 180 HCV infected patients by face to face interview; they were interviewed privately by using a structured questionnaire. P-values of ?0.05 were considered statistically significant. Out of 180 patients, 45% were males and 55% were females, the mean age of the cases was 33.18 years, regarding marital status 55.5% of the cases were single. The majority of the cases were diagnosed by routine screening. Most of the patients (70.7%) had no signs and symptoms at the time of diagnosis. In each patient at least two identifiable risk factors for getting HCV infection were reported. Among the patients that had genotype test, 67.2% of them infected with genotyope1. More than three-quarters of the participants had elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST). More future studied parameters and practical skills should be performed to significantly reduce the risk of HCV infection in Sulaimani.